When simplified, it should be 13/14
Answer:
a² + 4ab + 4b²
Step-by-step explanation:
Given
(a + 2b)²
= (a + 2b)(a + 2b)
Each term in the second factor is multiplied by each term in the first factor, that is
a(a + 2b) + 2b(a + 2b) ← distribute both parenthesis
= a² + 2ab + 2ab + 4b² ← collect like terms
= a² + 4ab + 4b²
Answer:
2.58333333333
Step-by-step explanation:
Hello there!
The first thing you must do is to find the slope of the line. To do this, find the negative reciprocal of your current equation. Since your current slope is 3, the negative reciprocal of that would be -1/3, which would be your slope.
Now that you have your slope, plug it into the slope intercept equation as well as your known points:
(1,8) m(slope)=-1/3
8=1(-1/3)+b
Now, solve for b:
8=1(-1/3)+b
8=-1/3+b
b=25/3
Now that you have the slope and the b value, you can conclude that your equation would be:
y=-1/3x+25/3